Prinzipien einer sprachübergreifenden Typologie von Lern-und Testaufgaben für elektronische Sprachlehrwerke - Tiutenko, Arthur; Koller, Gerhard (Fremdsprachenlernen online. Erfahrungen und Erkenntnisse im Projektverbund SprachChancen, 2007)
Technical solutions usually adopted for computer-based language teaching and testing materials were developed for purposes other than language learning. To understand the features offered by this technology and to formulate the requirements for their further development and improvement, the authors of language teaching materials need to know which types of learning tasks are realizable with modern technology in general. To establish a standard typology of learning and testing tasks, a system of classification categories is necessary that cannot be borrowed from any of the typologies already developed for traditional language teaching. A possible system of such criteria is discussed in the article.<br
Keywords: E-Learning